LEGAL PROTECTION FOR WORKERS IN THE PERSPECTIVE OF CERTAIN TIME EMPLOYMENT AGREEMENTS (PKWT) POST EMPLOYMENT CREATION LAW - Yana Sukma Permana (JILPR Journal Indonesia Law and Policy Review, 2023)
The protection of workers in Indonesia that must be carried out by every entrepreneur or company, namely regarding the maintenance and improvement of welfare. Specific Time Work Agreement (PKWT) is a work agreement between the employer and the employee who agrees to establish a work relationship for a certain time. In this PKWT system, work relationships are created because there is a job that must be completed by the worker within a certain period of time which is quite short, namely monthly or for several years. The research method used is normative juridical research. The results of the research show that in the Job Creation Law, there are several changes related to the provisions regarding work agreements for a certain time which are regulated in the Manpower Law. Then the Manpower Law only regulates provisions for the type of minimum wage, while in the Job Creation Law, namely the provisions in Article 81 Point 25, Article 88A to Article 88E is added between Article 88 and Article 89.